ANALISIS LAYANAN REPOSITORI UNIVERSITAS DIPONEGORO BERDASARKAN AKSESIBILITAS, TAMPILAN, DAN ISI: UPAYA PEMBERDAYAAN REPOSITORI BERBASIS RISET - Jumino, Jumino; Suwanto, Sri (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2019)
This study aims to analyze how the appearance, accessibility, contents, and to empower the IR UNDIP. The research method used is qualitative by using in-depth interviews, observation, documentation, and FGD as a method of data collection. Data processing is done by reducing and verifying data. The results showed that: (1) the display used by IR UNDIP was considered too simple, monotonous, and less user friendly; (2) the contents of the repository, must be complete and varied, according to the study programs available at the university; 3) increasing the ease of access of IR UNDIP needs to be considered, by providing instructions on how to log in by users and to increase the speed of wifi.